Komunikasi Lisan Bahasa Jepang di Tempat Kerja: Studi pada Japanese Speakers di Kawasan Industri KIIC - Nishfullayli, Sa’idatun; Dwiwardani, Wury; Kharismawati, Mery (KIRYOKU, 2025)
This study investigates the use of the Japanese language in workplace oral communication and some difficulties faced by Japanese speakers. ‘Japanese speakers’ refers to Indonesians who work as Japanese-speaking staff in Japanese companies. The data was obtained through applying questioner methods, Focus Group Discussions, and followed by in-depth interviews with respondents. The research respondents were Japanese speakers at KIIC (Karawang International Industrial City) of West Java. This study shows that Japanese language competence plays a significant role in smooth communication in the Japanese industry, especially in tier 2 and 3 companies. Japanese oral communication activities include internal (shanai) and external communication (shagai). Communication is generally used for completing work carried out through discussions or meetings, presentations to superiors and customers, suppliers, and communication with Japanese colleagues. In addition, because the Horenso concept is still strongly applied as an organizational communication system, the need to communicate in Japanese for hookoku, renraku, and soodan purposes is also significant. The difficulties experienced by Japanese speakers are seen in the difficulty of choosing expressions appropriate to the context and purpose of the conversation. This is partly due to their lack of understanding of the application of the concepts of ningen kankei and uchi-soto in Japanese business communication practices. Employees who have business Japanese competencies have a greater chance of advancing their careers. This research will continue to be refined to obtain results with a strong foundation as a basis for consideration in compiling business Japanese language teaching materials and improving the applied Japanese language curriculum to suit the needs of today's workplace.